Quantifying participation in, and the effectiveness of, remediating assessment in a university mathematics module. Issue 1 (2nd January 2019) - Howard, Emma; Meehan, Maria; Parnell, Andrew
Abstract: In Maths for Business, a large first-year mathematics module, the continuous assessment component comprises 10 weekly quizzes which combine to contribute 40% of the final module mark. If students did not receive the full five marks on their weekly quiz, they were provided with the opportunity to resubmit their corrected weekly quiz with an explanation of their error(s) for one additional mark. We refer to this process as 'remediation'. Of the students who had the opportunity to remediate, ∼70% did. Through examining learning management system data, we show that the remediation process encouraged students to access module resources. Furthermore, by using a Bayesian hierarchical model to account for students' level of participation, achievement and prior knowledge, we show that participation in the remediation process positively impacted the final examination marks of moderate to high-achieving students (based on initial continuous assessment marks). However, participation in the remediation process provided limited benefit to low-achieving students. We conjecture this is because these students had not achieved a level of understanding whereby participation in the remediation process could progress their knowledge.